2022
DOI: 10.3390/su14137645
|View full text |Cite
|
Sign up to set email alerts
|

An Optimal Dispatching Model for Integrated Energy Microgrid Considering the Reliability Principal–Agent Contract

Abstract: As the increasing penetration of sustainable energy brings risks and opportunities for energy system reliability, at the same time, considering the multi-dimensional differentiation of users’ reliability demands can further explore the potential value of reliability resources in Integrated Energy Microgrid (IEM). To activate the reliability resources in a market-oriented perspective and flexibly optimize the operational reservation in dispatch, an optimal dispatching model in IEM considering reliability princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The decommissioned power battery model is solved by a genetic algorithm (Chen, 2016;Hlal et al, 2019;Saini and Gidwani, 2022;Jiang et al, 2019), in which the original load (Wei et al, 2021) and peak adjusted curve are shown in Figure 2, and the output curve after peak shaving of the decommissioned power battery is shown in Figure 3. Assuming that the decommissioned power battery's service life and project life are both 5 years, no need exists for replacement costs at this time, and the annual investment cost and income of the decommissioned power battery are shown in Table 4.…”
Section: Economic Benefit Analysismentioning
confidence: 99%
“…The decommissioned power battery model is solved by a genetic algorithm (Chen, 2016;Hlal et al, 2019;Saini and Gidwani, 2022;Jiang et al, 2019), in which the original load (Wei et al, 2021) and peak adjusted curve are shown in Figure 2, and the output curve after peak shaving of the decommissioned power battery is shown in Figure 3. Assuming that the decommissioned power battery's service life and project life are both 5 years, no need exists for replacement costs at this time, and the annual investment cost and income of the decommissioned power battery are shown in Table 4.…”
Section: Economic Benefit Analysismentioning
confidence: 99%